Playful learning: tools, techniques, and tactics - Nicola Whitton (Association for Learning Technology, 2018)
Over the past decade, there has been an increased use of playful approaches to teaching and learning in higher education. Proponents argue that creating 'safe' playful spaces supports learning from failure, management of risk-taking, creativity and innovation, as well as increasing the enjoyment of learning for many students. However, the emergent field of playful learning in adulthood is under-explored, and there is a lack of appreciation of the nuanced and exclusive nature of adult play. This article will first examine the theoretical background to the field, providing an initial definition of 'playful learning' through the metaphor of the 'magic circle' and presenting a hypothesis of why play is important for learning throughout the life course. Second, it will frame the field by highlighting different aspects of playful learning: playful tools, techniques, and tactics. The third section of the article provides two case studies that exemplify different aspects of play: the EduScapes escape room design project, which uses playful failure-based learning, and the Playful Learning Conference, which employs playful principles to rethink the conference format. The article concludes by highlighting three central issues for this emerging field: lack of a research trajectory; the language of play; and unacknowledged privilege inherent in the use of playful learning.